Caracterização funcional e imunológica da proteína SmKI-1, um inibidor de serino protease do Schistosoma mansoni - Suellen Batistoni de Morais (2018)
Schistosoma mansoni is one of the main agents of schistosomiasis, which is the most important human helminthic infection in terms of global morbidity and mortality. Current schistosomiasis control strategies are mainly based on chemotherapy, but the development of a vaccine against this parasitic disease would contribute to a long-lasting decrease in disease spectrum and transmission. When it comes to vaccine candidates, numerous genes encoding S. mansoni proteins that are expressed at the mammalian host-parasite interface have been assessed. Among the most promising molecules are the proteins present in the tegument and digestive tract of the parasite. Although schistosomiasis represents a major public health problem in endemic countries, evidences show that S. mansoni downregulates inflammatory responses in many diseases. Fortunately, the control of inflammatory responses is extended to pathogen-derived antigens, leading us to study one S. mansoni Kunitz type protease inhibitor (SmKI-1), found in larval and adult phases of the parasite as a molecule capable of regulating different models of inflammatory diseases and as a vaccine candidate. First, we determine that recombinant (r) SmKI-1 and its Kunitz domain but not the C-terminal region possess inhibitory activity against trypsin and neutrophil elastase. To better understand the molecular basis of neutrophil elastase inhibition by SmKI-1, molecular docking studies were also conducted. Docking results suggest a complete blockage of neutrophil elastase active site by SmKI-1 Kunitz domain. Additionally, rSmKI-1 markedly inhibited the capacity of neutrophil elastase to kill schistosomes. In order to further investigate the role of SmKI-1 in the parasite, we designed specific siRNA to knock-down SmKI-1 in S. mansoni. SmKI-1 gene suppression in larval stage of S. mansoni robustly impact in parasite development in vitro and in vivo. To determine the ability of SmKI-1 to interfere with neutrophil migration and function, we tested SmKI-1 anti-inflammatory potential in different murine models of inflammatory diseases. Treatment with SmKI-1 rescued acetaminophen (APAP)-mediated liver damage, with a significant reduction in both neutrophil recruitment and elastase activity. In the model of gout arthritis, this protein reduced neutrophil accumulation, IL-1β secretion, hypernociception, and overall pathological score. Finally, we demonstrated the ability of SmKI-1 to inhibit early events that trigger neutrophil recruitment in pleural cavities of mice in response to carrageenan and also present some evidence that SmKI-1 does not affect the migration of other immune cells than neutrophils. We also evaluate the potential of SmKI-1 as a recombinant vaccine. Mice immunization with rSmKI-1, formulated with Freund’s adjuvant, induces a Th1-type response, as IFN-, and TNF- were detected in the supernatant of cultured splenocytes. The protective effect conferred by vaccination with rSmKI-1 was demonstrated by 51% reduction in the worm burden, 36% reduction in the number of eggs per gram of hepatic tissue, a 31% reduction in the number of granulomas, and 33% reduction in the area of liver granulomas.. In conclusion, SmKI-1 is a key protein in S. mansoni survival and it has the ability to inhibit neutrophil function as a promising therapeutic molecule against inflammatory diseases. As well as our data demonstrated that SmKI-1 is a potential candidate for use in a vaccine to control schistosomiasis.